Developmental Anatomy of Anther in the Red Dragon Fruit (Hylocereus polyrhizus Britton & Rose) - Utaminingsih Utaminingsih (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2025)
The developmental anatomy of the anther in Hylocereus polyrhizus (red dragon fruit) was examined to elucidate the sequential processes of microsporogenesis and microgametogenesis that underlie pollen formation. Flower buds were sampled at five developmental stages (1-5) and analyzed histologically using paraffin embedding and safranin staining. Anther length increased progressively by 96% from stages 1 to 4 and plateaued before anthesis, indicating growth cessation before pollen maturation. The anther wall followed a dicotyledonous pattern, comprising the epidermis, endothecium, middle layer, and tapetum. Early stages featured archesporial differentiation into primary parietal and sporogenous cells, followed by the formation of secondary parietal and sporogenous layers. The endothecium developed fibrous thickenings, while the binucleate, secretory tapetum provided nutrients for developing microspores and degenerated at maturity. Microsporogenesis proceeded from microspore mother cells to tetrads and solitary microspores, culminating in tricellular pollen grains at anthesis. These findings demonstrate that anther development in H. polyrhizus conforms to the typical dicotyledonous type, with characteristic features such as a secretory tapetum and fibrous endothecium. The results provide essential anatomical insight to support breeding programs, artificial pollination strategies, and reproductive biology studies of this economically valuable cactus species.